Pedati Model Online Learning in University - Astawan, I Gede; Widiana, I Wayan; Arafik, Muh (Journal of Education Technology, 2021)
Since the COVID-19 pandemic hit the world, various changes have occurred in the world of education. Teachers are required to be able to develop online learning so that learning activities can run smoothly. The purpose of this study was to analyze the effectiveness of online learning in universities. The research subjects were lecturers totalling 22 people. The research object includes the effectiveness of online learning programs in terms of context, input, process, and product. The approach used in this study is evaluative. The research model design used is the CIPP evaluation model (Context, Input, Process and Product Evaluation Model). The data were analyzed descriptively by calculating the percentage. Next, the data were analyzed by the T-Score formula. The level of effectiveness of online learning was analyzed through the quadrant of the "Glickman" model. The results of data analysis showed that online learning in PGSD, in terms of context, descriptively classified as very good, with an effectiveness percentage of 18.18%. Online learning at PGSD Undiksha in terms of input, descriptively is very good, with an effectiveness percentage of 0%. In terms of process, online learning at PGSD Undiksha is descriptively classified as very good, with an effectiveness percentage of -9.09%. In terms of products, online learning at PGSD Undiksha descriptively is classified as very good, with an effectiveness percentage of 18.18%. It can be concluded that the online learning that has been held is excellent and effective.